TRANSFORMASI GRUP MARBANDUT AN-NAWAWI TERHADAP KESENIAN MARAWIS PADA MASYARAKAT KAMALAKA KELURAHAN PANGGUNG JATI KECAMATAN TAKTAKAN KOTA SERANG, BANTEN - Dhio Licandra Agil; Suhaya Suhaya; Dadang Dwi Septiyan (Pendidikan Seni Pertunjukan Fakultas Keguruan dan Ilmu Pendidikan Universitas Sultan Ageng, 2023)
This study aims to find out and describe how the An-Nawawi marbandut group transforms into marawis art. The background of this research is the transformation of An-Nawawi's marawis art into An-Nawawi's marbandut which is influenced by people's requests to develop a more modern form of music. The transformation of musical forms in the An-Nawawi marbandut group made researchers use writing references. The research method uses descriptive qualitative through a case study approach with community objects/community leaders, members of An-Nawawi studio, and elders/founders of An-Nawawi studio. Data obtained through observation, interviews, and documentation. The research results obtained through the development and changes of the An-Nawawi marbandut group, researched directly to members of the An-Nawawi studio and the community regarding changes in terms of musical instruments and forms of marawis music featuring monotonous rhythmic music making marbandut a modern group in terms of clothing, musical instruments, formations in staging, and also forms of arrangement that can be enjoyed by every class. Keywords: transformation, art, marbandut an-nawawi.